Ocupar, resistir, produzir conhecimento - trajetórias de lutas no campus: a experiência de mulheres estudantes-trabalhadoras do IFSP-Jacareí - Esteves, Thaís Ribeiro (2025)
This thesis deals with the life trajectories of working-class women students, specifically at the Federal Institute of Education, Science and Technology of São Paulo Jacareí Campus (IFSP-JCR), seeking to understand how these trajectories affect school trajectories, particularly the conditions for school access and school permanence. We start from the premise that the trajectories of these women are marked by situations in which the need for survival overrides the human need for education; and that the problem of school permanence is not limited to objective living conditions, but also to the subjective dimension of social reality and the very structure of education systems. The historical-dialectical materialist method was our inspiration for the successive approaches to life trajectories, and the qualitative field research was based on the narratives of female Federal Institute of Education, Science and Technology of São Paulo Jacareí Campus students, both enrolled and graduated, about their life experiences, especially in relation to school education and the world of work. To this end, we interviewed nine enrolled students and analyzed five graduates’end-of-course memorials. Ethnographic exercises were also part of the research procedures, with the campus as the observation point. Based on the findings of the field research, we carried out a theoretical dialogue with intellectuals preferably from the Marxist tradition, but also from decolonial perspectives, and structured this work around three interrelated investigative axes: a) the study of memory and experience, based on the end-of-course memorials; b) the investigation of class, race/ethnicity and gender/sex relations as determinants and constituents of life trajectories, in interface with the world of work and school access and school permanence; c) the apprehension of the school unit in general, and the Federal Institute of Education, Science and Technology of São Paulo Jacareí Campus in particular, as a living, lived and disputed territory, where the contradictions for school access-permanence are expressed in everyday social life. Among the results of the research, we highlight: the potential of the end-of-course memorials as an act/movement of resistance and insurgency in the academic context, and as a production of knowledge that tensions the 'single history'; the repercussions of the social, sexual and racial division of labor, especially with regard to social reproduction activities, on women's student trajectories; the relevance of the “Quota Law”, Federal Law n. 12.711/2012, for the working class, and in particular for black women; the negative impacts of the COVID-19 pandemic and remote education on student permanence; the importance of the territorialities produced on campus with a view to student permanence. Finally, we reaffirm the importance of studies on trajectories as a contribution to the production of knowledge on school access and school permanence and show that student permanence, in order to be effective, must be conceived from the objectivity-subjectivity unity that makes up social reality